Microstructure and Magnetic Properties of Copper Mold Cast Nd–Fe–B Magnets Investigated by Phase‐Field and Micromagnetic Simulations. Issue 5 (2nd June 2022) - Li, Hao; Wang, Gang; Qiu, Zhaoguo; Zheng, Zhigang; Zeng, Dechang
Abstract : The effects of several factors, including alloy composition, cooling rate, and external magnetic field, on the microstructures and magnetic properties of Nd–Fe–B ternary alloy are explored in detail by using phase‐field and micromagnetic simulations during the copper mold casting process. It is found that the characteristic of regional distribution is formed due to the temperature gradient in the alloy, and that Nd19 Fe71.5 B9.5 (at%) exhibits the highest coercivity and pretty good comprehensive magnetic properties among all alloys studied, which can be interpreted by the refinement of Nd2 Fe14 B grain size and thickness of Nd‐rich grain boundary phase. The cooling rate has significant influence on the average grain size and the amount of amorphous phase. An increase of cooling rate results in a decrease of grain size and an increase of amorphous phase, which then affect the coercivity and remanence of the magnet. Applying an external magnetic field is demonstrated to be a good approach to enhance the coercivity and remanence by refining the grain size and restraining the formation of amorphous phase and T2 phase. Abstract : The effects of several factors, including alloy composition, cooling rate, and external magnetic field, on the microstructure and magnetic properties of Nd–Fe–B ternary alloy are explored in detail by using phase‐field and micromagnetic simulations during the copper mold casting process. Microstructure control of Nd–Fe–B is significant to improve its magnetic properties.